2019
DOI: 10.1101/634048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PilT and PilU are homohexameric ATPases that coordinate to retract type IVa pili

Abstract: 19Bacterial type IV pili are critical for diverse biological processes including horizontal gene 20 transfer, surface sensing, biofilm formation, adherence, motility, and virulence. These dynamic 21 appendages extend and retract from the cell surface. In many type IVa pilus systems, extension 22 occurs through the action of an extension ATPase, often called PilB, while optimal retraction 23 requires the action of a retraction ATPase, PilT. Many type IVa systems also encode a homolog 24 of PilT called PilU. How… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 59 publications
3
26
0
Order By: Relevance
“…3A). Interestingly, we and others recently demonstrated that V. cholerae's PilU works solely in conjunction with PilT instead of compensating for the lack of PilT (51,65), which suggests that it enhances the retraction force instead of behaving as an independent retraction enzyme, as was also suggested for P. aeruginosa (51,65,66).…”
Section: Competence and Pili Mutants Are Impaired In Transformationmentioning
confidence: 56%
“…3A). Interestingly, we and others recently demonstrated that V. cholerae's PilU works solely in conjunction with PilT instead of compensating for the lack of PilT (51,65), which suggests that it enhances the retraction force instead of behaving as an independent retraction enzyme, as was also suggested for P. aeruginosa (51,65,66).…”
Section: Competence and Pili Mutants Are Impaired In Transformationmentioning
confidence: 56%
“…Deletion of pilT prevents T4P retraction 16 and may thus reveal more subtle effects on pilus extension. T4P labeling in pilB, tfpB, and pilB tfpB mutants revealed that all three mutants were defective in T4P synthesis while pilT was intact (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…Mutants in A. baylyi were made using natural transformation as described previously 16 . Briefly, mutant constructs were made by splicing-by-overlap (SOE) PCR to stich 1) ~3 kb of the homologous region upstream of the gene of interest, 2) the mutation where appropriate (for deletion by allelic replacement with an antibiotic resistance cassette, or the fusion protein), and 3) the downstream region of homology.…”
Section: Construction Of Mutant Strainsmentioning
confidence: 99%
“…A detailed mechanistic understanding of the factors that promote pilus retraction, however, remains lacking in many T4P. For T4aP, pilus depolymerization is mediated by dedicated retraction ATPase motors commonly referred to as PilT and PilU (21, 22). However, even in the absence of these retraction motors, numerous T4aP retain the ability to retract (4, 21, 23, 24).…”
Section: Introductionmentioning
confidence: 99%